2020
DOI: 10.3390/ijerph17103651
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Swimming Disciplines—Can Women Outperform Men in Swimming?

Abstract: In recent years, the interest of female dominance in long-distance swimming has grown where several newspaper articles have been published speculating about female performance and dominance—especially in open-water ultra-distance swimming. The aim of this narrative review is to review the scientific literature regarding the difference between the sexes for all swimming strokes (i.e., butterfly, backstroke, breaststroke, freestyle and individual medley), different distances (i.e., from sprint to ultra-distances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 110 publications
2
37
1
Order By: Relevance
“…The performance times of the current study’s participants are lower than elite-level swimmers and highly trained master swimmers [ 4 , 8 ], which means that their technical skills could suffer a larger enhancement, and consequently, their performance has a great margin for improvement. Additionally, the current sample included both male and female swimmers, and this could have influenced the results as it is known that men swim faster than women, although there is a tendency for this gap to be reduced after the age of 30 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The performance times of the current study’s participants are lower than elite-level swimmers and highly trained master swimmers [ 4 , 8 ], which means that their technical skills could suffer a larger enhancement, and consequently, their performance has a great margin for improvement. Additionally, the current sample included both male and female swimmers, and this could have influenced the results as it is known that men swim faster than women, although there is a tendency for this gap to be reduced after the age of 30 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the actual study showed us that body composition related to gender specificity characteristics should be considered much more in the future as one of important issues within swimming science [ 50 ] along with the known bio-physical determinants related to swimming as: hydrodynamics, kinematics, energetics, and kinetics characteristics [ 41 , 49 ], anthropo-morphological characteristics [ 13 , 19 , 35 , 47 ], strength, and power capabilities [ 20 , 37 , 42 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…social background, training modalities, and genetics [20,50]. With the reduced gender difference in performance throughout recent years [1,2], lower age of elite and peak performance in female swimmers [4,27], and previously emphasized need for comprehensive performance PLOS ONE evaluations and identification of success factors specific to elite female athletes [28,29], for the present study, all female swimmers competing in single events at the 2018EC were included. As potential gender effects may exist, future studies should investigate AVCP, number of races per year, and age in male swimmers.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
“…During recent decades, improved performance of elite female athletes has narrowed the gap in performance to 8-12% compared to male athletes [1]. In swimming, depending on the discipline, the gender gap in performance is as low as 5% [1,2]. With the improved swimming performance and minimal gap between top swimmers [3], marginal differences distinguish between first and second place, such as at the 2018 European Long-Course Swimming Championships (2018EC), where the women's Freestyle final was won by only 0.01s and a 0.04% performance difference.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation